Studi Penelusuran (Tracer Study) Program Studi Pendidikan Guru Sekolah Dasar Tahun Lulus 2015-2019 - Sukamto; Ervina Eka Subekti; Fajar Cahyadi; Wawan Priyanto (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
A tracer study is a study conducted to determine the level of market absorption of graduates, the number of graduate unemployed, the suitability of subject matter to field needs, and the need for curriculum revision or renewal. The Primary School Teacher Education Program (PGSD) study program requires data for this purpose. Among them are graduates who work in the formal sector (teachers, lecturers, administrative staff, employees in business and industry, etc.) and in the informal sector. The purpose of this study was to (1) determine the extent of the absorption rate of PGSD S1 alumni in the job market. (2) Knowing the percentage of alumni waiting period before getting a job. (3) Obtaining data about the suitability of the ongoing curriculum with field needs. The results of this tracing study indicate that the absorption rate of PGSD S1 graduates in the job market is 87.92%. The waiting period for PGSD undergraduate graduates to get a job is 42.10% getting a job before graduating and on average it takes 3 months to get a job. The conformity between the subject matter and the field needs of elementary school teachers was 67.16% alumni. Among them are working as civil servants (government agencies) as teachers, as teachers in private schools. The alumni assessment is seen from several aspects, including: ethics, expertise in the field of science, foreign language skills, communication skills, teamwork, ability to develop themselves and the ability to use information technology. From all aspects the average rating given is good. The highest level of competence mastered by alumni at graduation (85.1%) is the ability to continue learning all the time and the lowest (69.25%) is the ability to speak English. One suggestion that can be put forward is about improving English language skills.